2014
DOI: 10.1104/pp.114.247767
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of a Deficit in Vitamin B6 Biosynthesis de Novo for Hormone Homeostasis and Root Development in Arabidopsis  

Abstract: Vitamin B6 (pyridoxal 5′-phosphate) is an essential cofactor of many metabolic enzymes. Plants biosynthesize the vitamin de novo employing two enzymes, pyridoxine synthase1 (PDX1) and PDX2. In Arabidopsis (Arabidopsis thaliana), there are two catalytically active paralogs of PDX1 (PDX1.1 and PDX1.3) producing the vitamin at comparable rates. Since single mutants are viable but the pdx1.1 pdx1.3 double mutant is lethal, the corresponding enzymes seem redundant. However, the single mutants exhibit substantial ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 82 publications
1
31
0
1
Order By: Relevance
“…A complete loss of vitamin B 6 biosynthesis de novo is embryo lethal (TambascoStudart et al, 2005;Titiz et al, 2006), while mutants in either one of the two catalytic PDX1 genes (PDX1.1 or PDX1.3) have short roots and are stress hypersensitive (Chen and Xiong, 2005;Titiz et al, 2006;Wagner et al, 2006;Boycheva et al, 2015). The latter phenotypes are remarkably similar to mutants in the salvage pathway kinase SOS4 (Rueschhoff et al, 2013), originally isolated due to their salt sensitivity .…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…A complete loss of vitamin B 6 biosynthesis de novo is embryo lethal (TambascoStudart et al, 2005;Titiz et al, 2006), while mutants in either one of the two catalytic PDX1 genes (PDX1.1 or PDX1.3) have short roots and are stress hypersensitive (Chen and Xiong, 2005;Titiz et al, 2006;Wagner et al, 2006;Boycheva et al, 2015). The latter phenotypes are remarkably similar to mutants in the salvage pathway kinase SOS4 (Rueschhoff et al, 2013), originally isolated due to their salt sensitivity .…”
Section: Introductionmentioning
confidence: 51%
“…The latter phenotypes are remarkably similar to mutants in the salvage pathway kinase SOS4 (Rueschhoff et al, 2013), originally isolated due to their salt sensitivity . Recently, the phenotypes associated with pdx1.1 and pdx1.3 have been linked primarily to a perturbation in ethylene and auxin homeostasis (Boycheva et al, 2015), two phytohormones that require PLP as a cofactor for their biosynthesis. By contrast, mutants partially impaired in the expression of the salvage pathway enzyme PDX3 were reported to be morphologically indistinguishable from wild-type plants when grown on soil under normal conditions but hypersensitive to high sucrose levels, high light, and chilling (González et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Histochemical GUS expression analyses was carried out essentially as described by Boycheva et al (2015). Images were captured with a Leica MZ16 stereomicroscope equipped with an Infinity 2 digital camera (Leica Microsystems).…”
Section: Gene Expression Analysesmentioning
confidence: 99%
“…New inhibitors that may show improved specificity for ACS were recently identified (Lin et al, 2010); these compounds do not compete with PLP, reducing side effects on other PLP-dependent enzymes. Nonetheless, severe effects on seedling root growth should be expected for all of these inhibitors of ethylene synthesis, because reduced ethylene synthesis appears to be a primary defect in PLP-deficient roots, leading to impairments in auxin synthesis and distribution and in apical meristem function (Boycheva et al, 2015). Intriguingly, genetic analysis revealed an essential embryonic requirement for ACS function (but not ethylene signaling) in Arabidopsis (Arabidopsis thaliana; Tsuchisaka et al, 2009), and additional work has suggested that ACC may act in an ethylene-independent mode to signal loss of cell wall integrity (Xu et al, 2008;Tsang et al, 2011).…”
Section: Hardware Of the Biosynthetic Pathwaymentioning
confidence: 99%